PENGARUH MOTIVASI DAN BUDAYA ORGANISASI TERHADAP KINERJA KARYAWAN YAYASAN SAHABAT YATIM INDONESIA CABANG TANGERANG SELATAN - Septiana, Fadhila Alroof; Sudarso, Eko (CV. KAMPUSA AKADEMIK PUBLISING, 2025)
This study aims to examine the influence of motivation and organizational culture on employee performance at the Indonesian Yatim Friends Foundation, South Tangerang Branch. A quantitative research method was used, with survey data collected from 84 respondents through structured questionnaires. The independent variables in this study are motivation (X₁) and organizational culture (X₂), while the dependent variable is employee performance (Y). Validity testing showed all questionnaire items to be valid, with r count > 0.214. Reliability testing produced Cronbach’s Alpha scores of 0.848 for motivation, 0.771 for organizational culture, and 0.821 for employee performance, indicating reliable instruments.The multiple linear regression analysis yielded the following equation:Y = 17.175 + 0.295X₁ + 0.269X₂ The coefficient of determination (R²) was 0.230, meaning motivation and organizational culture together explain 23.0% of the variance in employee performance.Partially, motivation significantly affects performance (t count = 3.012 > 1.991; sig = 0.003 < 0.05), while organizational culture also has a significant effect (t count = 2.458 > 1.991; sig = 0.016 < 0.05). Simultaneously, the F-test shows F count = 12.112 > F table = 2.72, with a significance of 0.000